Analisis Kelayakan Usaha Pada Keripik Nangka UMKM Sang Bintang Kabupaten Ketapang - Indriawan, Rois (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2023)
This research was conducted to evaluate the income level and feasibility of the micro, small, and medium enterprise (UMKM) "Sang Bintang" based on Return on Investment (ROI). The study employed purposive sampling method. Data collection techniques included primary data (through interviews, observations, and documentation with the business owner) as well as secondary data. The research findings revealed that the Return on Investment (ROI) from the jackfruit chips business is approximately 0.0195%. This indicates that the profit obtained is slightly higher than the initial investment costs, albeit within a very small range. A low ROI like this suggests that the investment yielded relatively modest profits compared to the amount of money invested.